HUBUNGAN DUKUNGAN SOSIAL DAN PEMANFAATAN BUKU KIA DENGAN KUNJUNGAN ANTENATAL CARE (ANC) - Indreswati indreswati; Vitria Komala Sari; Yuni Melpa Julisa (Maternal Child Health Care, 2022)
The guguk panjang health center is the national health center with the lowest K4 coverage and experienced a decline from 84.3% to 53.32% in 2018. This study aims to determine the relationship between social support and utilization of MCH books with antenatal care visits (ANC) in the working area of the health center the length of the Bukittinggi city in 2018.The type of this research was descriptive analytic with a cross sectional study approach. It was conducted on November to December 2018 in Guguk Panjang Community Health Center. The populations were all TM III pregnant women. They were 48 people. Then, by using total sampling technique, all of the populations were chosen as the samples. The data were collected trough questionnaire sheets. Next, it was analyzed by univariate and bivariate analysis.The results of this research showed that 55.3% of respondents had poor social support. Then, 51.1% of them used KIA books well. Last 57.4% of respondents had regular ANC. Moreover, there was a correlation between social support (p = 0.041, OR = 4.364) and utilization of the MCH books (p = 0.028, OR = 4,667) toward Antenatal Care (ANC) visits. In short, it can be concluded that social support and utilization of MCH books were significantly associated with Antenatal Care (ANC) visits. Then, it is expected to all parties, especially pregnant women able to utilize MCH books in order to enlarge their and it may change their behavior to do better Antenatal Care visits.Keywords               : Antenatal Care Visits, Social Support, Utilization of MCH books